2007
DOI: 10.1038/sj.mt.6300222
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of SMN Function: Delivery of a Trans-splicing RNA Re-directs SMN2 Pre-mRNA Splicing

Abstract: Spinal muscular atrophy (SMA) is caused by loss of survival motor neuron-1 (SMN1). A nearly identical copy gene called SMN2 is present in all SMA patients; however SMN2 produces low levels of functional protein due to alternative splicing. Recently a therapeutic approach has been developed referred to as trans-splicing. Conceptually, this strategy relies upon pre-messenger RNA (pre-mRNA) splicing occurring between two separate molecules: (i) the endogenous target RNA and (ii) the therapeutic RNA that provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 47 publications
0
88
0
1
Order By: Relevance
“…In particular, Coady and coworkers have developed a therapeutic trans-splicing RNA base-pairing with the intron 6 of SMN2 and containing the SMN1 exon 7 sequence. 151 The final product Figure 4. Scheme depicting splicing correction strategies for SMA based on in vivo expressed rNAs (A) SnrNA-based strategies.…”
Section: Smn2 Exon 7 Inclusionmentioning
confidence: 99%
“…In particular, Coady and coworkers have developed a therapeutic trans-splicing RNA base-pairing with the intron 6 of SMN2 and containing the SMN1 exon 7 sequence. 151 The final product Figure 4. Scheme depicting splicing correction strategies for SMA based on in vivo expressed rNAs (A) SnrNA-based strategies.…”
Section: Smn2 Exon 7 Inclusionmentioning
confidence: 99%
“…18 SMaRT has been shown to repair defective pre-mRNA molecules in cultured mammalian cells, xenografts and animal models of human disease including cystic fibrosis, 12 hemophilia A (factor VIII deficiency), 13 X-linked CD40 ligand immunodeficiency, 14 human apolipoprotein A1, 15 DNA protein kinase deficiency, 19 epidermolysis bullosa simplex with muscular dystrophy 20 and spinal muscular atrophy. 21 In DM1, a strategy to remove or correct mutant mRNA is appropriate in view of evidence that the accumulation of mutant mRNA in the nucleus is the primary basis of the disease. 3,22 Approaches targeted at the mRNA level to remove mutant mRNA, namely the use of antisense, 23 nuclear-retained hammerhead ribozyme 4 and siRNA, 5 have been shown to be able to remove mutant mRNA in in vitro DM1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This promising perspective seems to be greatly boosted by recent developments in SMN/SMA studies in which technologies such as trans-splicing, bifunctional oligonucleotides, and anti-sense oligonucleotides very specifically increase the inclusion of exon 7 into SMN2 mRNA (Fig. 2) (Baughan et al, 2006;Coady and Lorson, 2010;Coady et al, 2007;Dickson et al, 2008;Hua et al, 2010;Lorson et al, 2010;Osman et al, 2012;Shababi and Lorson, 2011;Shababi et al, 2011;Skordis et al, 2003). In particular, the effectiveness of anti-sense oligos in animals with SMA has excited the scientific community so that SMA may be treatable in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been comprehensively explored by Lorson's group during the last few years to correct SMN2 splicing. They optimized trans-splicing strategies and demonstrated that transsplicing increases exon 7 insertion into SMN2 mRNA and extend the life of animals with SMA (Coady and Lorson, 2010;Coady et al, 2007;Shababi and Lorson, 2011;Shababi et al, 2011).…”
Section: Sma Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation